Determinants of poverty among local rice processors in Kwara State, Nnigeria - M. F. Salami; R. O. Babatunde; O. E. Ayinde; E. I. Adeoti (Trakia Journal of Sciences)
This study accessed the extent and determinants of poverty among local rice processors in Kwara state. Primary data were obtained through questionnaire and interview schedule. Data were subjected to descriptive statistics, Foster-Greer-Thorbecke (FGT) class of decomposable poverty and logistics regression analysis. The result of the descriptive statistics show that majority (97.5%) of the rice processors are female and substantial number (83.33%) of the rice processors do not have other source of income apart from rice processing. The result of the FGT class of decomposable poverty showed that poverty is more intense or severe in households with small household size. The results of the logit regression showed that gender (female), educational status, income and household size were significant poverty determinants in the study area. Higher educational status, larger income and larger household size are poverty reducing while increase in gender (female) is poverty enhancing. It is therefore recommended that government and other stakeholders should invest more in the education of the rice processors. The rice processors should as well be encouraged to engage secondary occupation so as to earn more income. Also, men should be encouraged to be involved in rice processing in the study area